Building a 2D game physics engine : using HTML5 and JavaScript - Tanaya, Michael; Chen, Hua Ming; Pavleas, Jebediah; Sung, Kelvin, 1964- (Apress, 2017)
Build your very own 2D physics-based game engine simulation system for rigid body dynamics. Beginning from scratch, in this book you will cover the implementation technologies, HTML5 and JavaScript; assemble a simple and yet complete fundamental mathematics support library; define basic rigid body behaviors; detect and resolve rigid body collisions; and simulate collision responses after the collisions. In this way, by the end of Building a 2D Game Physics Engine, you will have an in?depth understanding of the specific concepts and events, implementation details, and actual source code of a physics game engine that is suitable for building 2D games or templates for any 2D games you can create and can be played across the Internet via popular web?browsers. What You'll Learn Gain an understanding of 2D game engine physics and how to utilize it in your own games Describe the basic behaviors of rigid bodies Detect collisions between rigid bodies Resolve interpretations after rigid body collisions Model and implement rigid body impulse responses Who This Book Is For Game enthusiasts, hobbyists, and anyone who is interested in building their own 2D physics game engines but is unsure of how to begin.